2008
DOI: 10.1038/nsmb.1528
|View full text |Cite
|
Sign up to set email alerts
|

The exosome contains domains with specific endoribonuclease, exoribonuclease and cytoplasmic mRNA decay activities

Abstract: The eukaryotic exosome is a ten subunit 3′ exoribonuclease complex responsible for many RNA processing and degradation reactions. How the exosome accomplishes this is unknown. We show that the PIN domain of Rrp44 is an endoribonuclease. The activity of the PIN domain prefers RNA with a 5′ phosphate, suggesting coordination of 5′ and 3′ processing. We also show that the endonuclease activity is important in vivo. Furthermore, the essential exosome subunit Csl4 does not contain any essential domains, but its zin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
319
3
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 272 publications
(338 citation statements)
references
References 58 publications
6
319
3
6
Order By: Relevance
“…In addition, the N terminus of Rrp44p contains an endonucleolytic PIN domain. Either active site is sufficient for viability; however, simultaneous inactivation of both nuclease activities results in a lack of cell growth (11)(12)(13). Although the biological substrates of the Rrp44p endonuclease have not been fully elucidated, the synthetic lethality observed upon inactivation of the Rrp44p nucleases implies that they have overlapping functions.…”
Section: Dis3 | Saccharomyces Cerevisiaementioning
confidence: 99%
“…In addition, the N terminus of Rrp44p contains an endonucleolytic PIN domain. Either active site is sufficient for viability; however, simultaneous inactivation of both nuclease activities results in a lack of cell growth (11)(12)(13). Although the biological substrates of the Rrp44p endonuclease have not been fully elucidated, the synthetic lethality observed upon inactivation of the Rrp44p nucleases implies that they have overlapping functions.…”
Section: Dis3 | Saccharomyces Cerevisiaementioning
confidence: 99%
“…The sole RNase activity of the eukaryotic exosome comes from the tenth protein, npg www.cell-research.com | Cell Research Rrp44 (Dis3), which attaches to the bottom of the core complex. Rrp44 is a multi-domain protein with a processive hydrolytic exonuclease activity at its C-terminal region, which is homologous to bacterial RNase II, and a relatively weak endonuclease activity at its N-terminal region [10][11][12]. Previous structural studies have shown that Rrp44 specifically interacts with Rrp41, Rrp43 and Rrp45 of the core complex, aligning with the central channel's exit of the core complex [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Both of these minimal exosomes are able to interact with the catalytic subunit and rNa. it has been proposed previously that more than one conformation of the exosome exists in fly cells (andrulis et al, 2002) and that some mutations in yeast csl4 disrupt only specific exosome functions (Schaeffer et al, 2009;van Hoof et al, 2000), which is con sistent with the existence of multiple forms of the exosome. Whether the seven mer and eight mer minimal exosomes described by the Lorentzen group are formed and function in vivo remains to be determined.…”
Section: Flexibility Within the Exosomementioning
confidence: 98%